EFFECTIVENESS OF MODERN WOUND CARE MANAGEMENT BASED ON EVIDENCE-BASED NURSING - Ossi Dwi Prasetio; Shulhan Arief Hidayat; Manggar Purwacaraka; Rio Ady Erwansyah (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Chronic wounds pose a challenge in healthcare due to the risk of infection, complications, amputations, and reduced quality of life for patients. Technological advances have led to the emergence of various modern wound care methods that are more effective than conventional methods. Methods: This study employed a literature review with the PRISMA approach. Articles were searched through Scopus, PubMed, ProQuest, and Google Scholar databases using keywords related to modern wound care and wound healing. Fifteen articles meeting the inclusion criteria were analyzed and synthesized. Results: The review showed that various modern wound care interventions, such as smart dressings, Negative Pressure Wound Therapy (NPWT), biological therapy, modern debridement, complementary therapies, and multidisciplinary approaches, can accelerate granulation tissue formation, enhance re-epithelialization, reduce infection and biofilm, and accelerate the healing process. NPWT is one of the interventions with the most consistent evidence of effectiveness, especially in complex and chronic wounds. Conclusion: Modern wound care management based on evidence-based practice has been shown to be more effective in improving wound healing through a combination of technology, regenerative therapy, and a holistic, patient-centered approach.